Antifungal activity of silver nanoparticles against Candida spp - Panácek, Ales; Kolár, Milan; Vecerová, Renata; Prucek, Robert; Soukupová, Jana; Krystof, Vladimír; Hamal, Petr; Zboril, Radek; Kvítek, Libor (Biomaterials, 2009)
The antifungal activity of the silver nanoparticles (NPs) prepared by the modified Tollens process was evaluated for pathogenic Candida spp. by means of the determination of the minimum inhibitory concentration (MIC), minimum fungicidal concentration (MFC), and the time-dependency of yeasts growth inhibition. Simultaneously the cytotoxicity of the silver NPs to human fibroblasts was determined. The silver NPs exhibited inhibitory effect against the tested yeasts at the concentration as low as 0.21 mg/L of Ag. The inhibitory effect of silver NPs was enhanced through their stabilization and the lowest MIC equal to 0.05 mg/L was determined for silver NPs stabilized by sodium dodecyl sulfate against Candida albicans II. The obtained MICs of the silver NPs and especially of the stabilized silver NPs were comparable and in some cases even better than MICs of the conventional antifungal agents determined by E-test. The silver NPs effectively inhibited the growth of the tested yeasts at the concentrations below their cytotoxic limit against the tested human fibroblasts determined at a concentration equal to 30 mg/L of Ag. In contrast, ionic silver inhibited the growth of the tested yeasts at the concentrations comparable to the cytotoxic level (approx. 1mg/L) of ionic silver against the tested human fibroblasts.
Keywords: Cell Line; buněčné linie; stříbro; Candida; Silver; Humans; Antifungal Agents; Metal Nanoparticles; kovové nanočástice; lidé; antifungální látky; viabilita buněk; Cell Survival